A Necessary Addiction: Student Conceptualizations of Technology and Its Impact on Teaching and Learning. Issue 1 (2nd January 2018) - Bauer, Laurie B.
Abstract : The near constant use of technology today has led to widespread changes in the way literacy is imagined, used, and theorized. Since college students spend a significant amount of time using and being involved with various acts of technology, there is no doubt that their literate lives are changing and adapting as well. Although most college-aged students would call themselves technologically literate, many still struggle with the literacy demands of college; therefore, postsecondary literacy research needs to focus on these changes and how they impact the literate lives of college students. This study aims at discovering students' views and beliefs regarding technology. Utilizing metaphor analysis, students' elicited metaphors were studied to determine their conceptualizations of technology in order to gather useful information about how technology is impacting their literate lives and how educators can best bridge common out-of-school literacy practices with academics.